Pengaruh Tingkat Pendidikan dan Pengetahuan terhadap Kepemilikan BPJS Ketenagakerjaan pada Relawan Penanggulangan Bencana Gunung Semeru Tahun 2021 - Prasetyo, Rahmat Adi; Chabibah, Afifa Nur; Haksama, Setya (citeus, 2022)
Humanitarian workers or volunteers are included in non-wage workers which are one of the sectors that can be protected by BPJS Ketenagakerjaan. The research results in 6 provinces show that BPJS Ketenagakerjaan participants are 3.7 percent and haven’t reached the 6 percent target. Based on the interviews results with deskrelawan admin also stated that many volunteers didn’t have BPJS Ketenagakerjaan. Individual awareness in insurance is marked by openness in accepting and utilizing insurance. This awareness can be influenced by various factors, including: age, gender, occupation, education. This research is quantitative research with cross-sectional design. It is a descriptive analysis with a test of the influence between dependent and independent variable. This research involved 115 respondents who were volunteers for the Mount Semeru eruption disaster management. The results of this study indicate that education has an influence on BPJS Employment ownership (p-value is 0.002 and OR is 3.54). Meanwhile, knowledge also affects BPJS Employment ownership with a sig value of 0.001 with an OR value of 11 for high knowledge and an OR value of 2.6 for moderate knowledge. Higher education haa s 3.54 times higher effect on BPJS Employment ownership than those with low education, while high knowledge has an 11 times greater effect on BPJS Employment ownership compared to those with low knowledge.